PERSEPSI PENDENGAR TERHADAP ACARA SENANDUNG SENJA DAN INFORMASI RADIO ABDI PERSADA FM BANJARMASIN - M.S. Sailillah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
This study aims to determine the influence of motives and satisfaction withlistener loyalty programs humming dusk and information Banjarmasin Abdi Persada Fm Radio . . The underlying motives for using media audiences and the satisfaction he felt after using these media will affect the loyalty to a media audience .According to Childers , et al . , ( 2001) in Christodoulides and Michaelidou ( 2010) , can be used as a basic motif that is useful in understanding the behavior of qkonsumensuch as satisfaction and loyalty . multiple linear regression analysis . results of the studyindicate that the motif of information and entertainment motifs are motifs listenerswhich has been able to be satisfied by the program humming dusk and information Banjarmasin Abdi Persada Fm Radio . While the motives of personal identity and personal relationships have not been satisfied . Directly proportional to the low condition of listener loyalty . The results of a qualitative descriptive analysis showed that the motives and satisfaction and a significant positive effect on the listener loyalty . Keywords : Motives , Kepuasan Pendengar Radio , Use of Media